Sams Teach Yourself SQL in 24 Hours (5th Edition) (Sams Teach Yourself -- Hours) - Stephens, Ryan (Pearson Education, 2011)
In just 24 sessions of one hour or less, you’ll learn how to use SQL to build effective databases, efficiently retrieve your data, and manage everything from performance to security! Using this book’s straightforward, step-by-step approach, you’ll learn hands-on through practical examples. Each lesson builds on what you’ve already learned, giving you a strong real-world foundation for success. The authors guide you from the absolute basics to advanced techniques—including views, transactions, Web data publishing, and even powerful SQL extensions for Oracle and Microsoft SQL Server!